THE WORD AS 'VAC' AND THE SILENCE OF JOY: A FEMININE INTERPRETATION - Mataji, Vandana (Journal of Dharma, 1992)
In the Christian Tradition we are used to thinking of God as "the Word" more than Silence; and the Word of God being more 'male' than as 'female'. Here I should like to try an approach to the Word as Vãc or speech, which is feminine even grammatically, and speech rather than the Word as Sabda, or sound. By Vãc or speech I understand a gentler, quieter witness and by Sabda or Word, a more forceful masculine proclamation and verbal testimony.